Influence of the Molecular Weight of Polyethylene Glycol and Polyethylene Oxide on the Adsorption and Electrochemical Properties of the Titania/ Electrolyte Solution Interface - S. Chibowski; M. Paszkiewicz (Adsorption Science & Technology)
The kinetic and adsorption properties of non-ionic polymers, i.e. polyethylene glycol (PEG) and polyethylene oxide (PEO), on a titania surface were compared. The influence of the molecular weight and pH on the electrical properties of the solid/polymer solution interface were examined. The main factors responsible for the zeta potential and surface charge of TiO2 were defined. A possible mechanism for the changes in zeta potential due to the pH of the solution and changes in the molecular weight of the polymer was proposed from a comparison of the data obtained. Thickness measurements of the adsorption layer of PEG and PEO on titania confirmed the influence of the molecular weight on the conformation of the polymer chains in the surface layer of the solid.